Uji Kualitas Log Kayu Kawui (Vernonia arborea Burch Ham) Setelah Masa Simpan Lima Tahun: Kawui Wood Quality Test after Five Years Storage - Indrayanti, Lies; Siska, Grace; Afentina, Afentina; Wardhani, Isna (HUTAN TROPIKA, 2024)
This study aims to understand physical and mechanical traits of kawui wood after storage period of five years. Further, this study aims to understand how the five years storage period influence the quality of kawui wood, and thus, it ensures the expected standard quality of the wood after longer term of storage. The method used in this study is Complete Randomized Design factorial, whereby the first factor is tree. The second factor is the year which are year 1 (2019) and year 2 (2024). Each of the factor is executed within tree repetition. The making of test samples followed the DIN 52-183 and 52 182 standards. The results show that for the density, MoR and MoE parameters of kawui wood with a storage period of five years is a significant effect except for the water content parameter. The average water content value of the research results was 14%, still within the reference design value of SNI 7973: 2013 which sets the water content at 19%. The decrease in density values showed the same tendency as the decrease in MoR and MoE values. The decrease in MoR value with a storage period of five years ranged from 12.5-25%., while the decrease in MoE value with a storage period of 5 years ranged from 3-6% and was included in the E8 quality of SNI 7973: 2013 regulations